2021
DOI: 10.3390/cells10010111
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine-Mediated Crosstalk between Immune Cells and Epithelial Cells in the Gut

Abstract: Cytokines are small proteins that are secreted by a vast majority of cell types in the gut. They not only establish cell-to-cell interactions and facilitate cellular signaling, but also regulate both innate and adaptive immune responses, thereby playing a central role in genetic, inflammatory, and infectious diseases of the gut. Both, immune cells and gut epithelial cells, play important roles in intestinal disease development. The epithelium is located in between the mucosal immune system and the gut microbio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
53
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(62 citation statements)
references
References 204 publications
2
53
0
1
Order By: Relevance
“…As ESPs administration could decrease the accumulation of macrophages and alleviate HF-induced colonic inflammation ( Figure 4 ), we speculated that ESPs maybe indirectly reshape gut microbiota via potential anti-inflammatory or immunoregulatory actions that suppress the gut pathology and protect against dysbiosis. In fact, previous studies have showed that several cytokines can influence and shape the microbial community within the gut lumen ( 56 ). Moreover, intestinal inflammation can lead to an altered composition of gut microbiota, known as dysbiosis, that is associated with functional changes in the microbial transcriptome, proteome or metabolome ( 57 ).…”
Section: Discussionmentioning
confidence: 99%
“…As ESPs administration could decrease the accumulation of macrophages and alleviate HF-induced colonic inflammation ( Figure 4 ), we speculated that ESPs maybe indirectly reshape gut microbiota via potential anti-inflammatory or immunoregulatory actions that suppress the gut pathology and protect against dysbiosis. In fact, previous studies have showed that several cytokines can influence and shape the microbial community within the gut lumen ( 56 ). Moreover, intestinal inflammation can lead to an altered composition of gut microbiota, known as dysbiosis, that is associated with functional changes in the microbial transcriptome, proteome or metabolome ( 57 ).…”
Section: Discussionmentioning
confidence: 99%
“…Inflammatory reactions are modulated by inflammatory mediators, which are released by sensitive leukocytes (such as macrophages, dendritic cells, or mast cells) in the tissue when pathogens or disturbed tissue homeostasis are detected. Mediators may also be released by endothelial cells, by epithelial cells, by fibroblasts or by PMNs themselves upon activation ( 4 , 37 , 39 , 40 ).…”
Section: The Role Of Neutrophils In Non-specific Immune Defensementioning
confidence: 99%
“…Many intestinal cell types secrete small proteins or cytokines to accelerate cell signaling, activate cell-cell interactions, and control both innate and adaptive immune responses in the gut. These epithelial cells are located between the immune system of the mucosa and the gut microbiome, acting as an arbiter in both directions: intestinal epithelial cells respond to cytokines of immune cells and their response reshapes the microbiome, so through this cytokine signaling network, important functions are tightly controlled such as proliferation, cell death, permeability, microbial interaction, barrier maintenance, keeping the host’s health safe [ 55 ].…”
Section: Microbiome and The Immune Systemmentioning
confidence: 99%